(untitled) (Research, Society and Development, 2021)
The present study aimed to develop a model to predict the service life of external wall coverings in mortar with paint finish, based on the state of degradation of 28 buildings in the city of Recife, Brazil. The area of the coating affected by different pathological manifestations was measured, and a numerical index to describe the severity of the degradation of the coating (Sw) was calculated. As a result of this index, degradation curves were constructed based on intrinsic factors (cardinal orientation, texture, color and presence of constructive details) and extrinsic factors (distance from the sea and proximity to polluting sources). In the analyzed samples, there was predominance of stains, and in less extent, cracks and detachments. The results showed that the cardinal orientation is the most influent characteristic in the durability of this coating system. The results obtained clearly demonstrate the applicability of the model in the study of the degradation of coatings, contributing to the development of maintenance actions focused on the most important factors in the degradation of coatings.